Industrial Tourism as a Means of “Made in China” Reputation Improvement - Novoselova, Olga (Journal of Tourism, Sustainability and Well-being, 2021)
The article discusses the development of industrial tourism as a way of country-of-origin promotion. The paper presents a study which focuses on determining the current situation of industrial tourism, and the peculiarities of international communication strategies in promoting industrial tourism in China. The methods of online international communication in promoting industrial tourism in China were analyzed in this study, specifically Shanghai’s strategy of promotion was chosen where 17 industrial tourism examples received additional governmental support and advocacy. As a result, it was found that the mechanism of international promotion is largely related to existing standards, new communication technologies are used in limited ways, and all the provided information is mostly not adopted for international target audiences. The analysis is made on the basis of theoretical and empirical data, both available by free access and the author’s data. The methods of data collection are analysis of scientific literature and content analysis of Internet sources.